The reckoning : our nation's trauma and finding a way to heal - Trump, Mary L. (New York : St. Martin's Press, 2021)
This book examines America$1 (Bs national trauma, rooted in our history but dramatically exacerbated by the impact of current events and the Trump administration$1 (Bs corrupt and immoral policies, and reveals what must be done to rebuild our faith in leadership.s
Includes bibliographical references (pages 185-193).
Keywords: Trump, Donald, -- 1946-; Collective memory; National characteristics; Political corruption -- United States; United States -- Social conditions -- 21st century; Collective memory -- United States; United States -- Politics and government -- 2017-2021.